Functionalized CNT-azobenzene-PVA-based self-healing aqueous gel as a conductive photo-responsive actuator - Narayanan, Aswini; Bhagyasree, T. M.; Torris, Arun; Babu, Sukumaran Santhosh (Journal of materials chemistry C, 2023)
Conductive gels have gained attention from researchers owing to potential applications in flexible displays, implantable medical devices, touch panels, wearable electronic skin, sensors, soft robotics, etc. Photo-responsive conductance switching gels can make their way into various applications, including contact-free remote-controlled manipulation of the materials, implantable synthetic organs, and optical switches. Herein, we report an aqueous gel with boronic acid containing azobenzene crosslinker as the light-responsive part that can undergo reversible cis-trans isomerization on irradiation with UV-vis light and catechol functionalized single-walled carbon nanotube as a conductive part producing a self-healing aqueous gel with PVA. The 3D crosslinked gel network formed through the formation of boronic ester and hydrogen bonding between hydroxyl and boronic acid groups was confirmed using scanning electron microscopy, X-ray microtomography, and rheological experiments. Rheology results show that gel is a viscoelastic material with immediate self-healing properties. The presence of functionalized SWCNT in the gel matrix enhances the stability and results in a conductivity of up to 3.5 S cm-1 with a loading of 5 wt%. The gel network exhibits a photoresponsive conductance switching from 10 to 60 mu A with UV and visible light irradiation, respectively. The molecular level motions during the isomerization of azobenzene lead to macroscopic dynamic changes that can find applications in soft actuators. The photoresponsive conductivity switching and dynamic movements of the films make the present material suitable for contact-free switching applications. Responsive conductive gels have gained attention owing to potential applications in flexible displays, implantable medical devices, touch panels, wearable electronic skin, sensors, soft robotics, and related areas.
Keywords: Cyclodextrins; Supramolecular Hydrogels,